Research interdisciplinarity and citation impact: a network analysis of social networking sites research - Zheng, Jingwei (2023)
The influence of interdisciplinary research has become a trending topic in library and information science. However, research examining the influence of interdisciplinarity on scholars is still limited. This current study examines the interdisciplinarity from the author co-citation network approach. We focus on the field of social networking sites (SNS) research, namely studies about online platforms that people use for networking (e.g., Facebook), and examine whether interdisciplinarity would promote academic impact. About 2,489 articles in the field of SNS published from 2014 to 2016 were retrieved, with 611 first authors cited by those articles identified. The interdisciplinarity of the scholar was assessed in the author co-citation networks using two indexes: betweenness centrality and constraint. We identified four primary disciplines of SNS research in 2014 to 2016. Interdisciplinarity indexes were used to predict the scholarly impact in this field in the next 3-year interval (2017–2019), measured by citation counts. We found that citation number was predicted by betweenness centrality but not by constraint. Theoretical and practical implications of interdisciplinarity in research activities are discussed.